Effect of adding systematic desensitization to goal-directed paradigm on risk of falling in patients with stroke: a randomized controlled trial - Abdelfadil, Heba Mohammed Gaber; Fahmy, Ebtisam Mohamed; Abdelmegeed, Shimaa Mohamed; Zakaria, Hoda Mohammed; Darwesh, Ashraf Ahmed; Kadry, Ahmed Mahmoud; Elsayed, Shereen Hamed; Aboeleneen, Ahmed M.; Alshimy, Ahmed Magdy (Frontiers in Neurology, 2024)
Background Improvement in rehabilitation outcomes for patients suffering from chronic stroke can be attained through systematic desensitization of their fear of falling, which in turn reduces the risk of falling. Purpose This study aimed to examine the effect of adding systematic desensitization to a goal-directed paradigm on functional performance, balance, risk of falling, and fear of falling among chronic ischemic stroke patients. Methodology Two equally sized groups, each comprising 40 stroke patients of both sexes, were randomly divided. For 8 weeks, Group A received three sessions per week of combined treatment consisting of systematic desensitization and a goal-directed paradigm, while Group B received only the goal-directed paradigm. The Timed Up and Go (TUG) test and Dynamic Gait Index (DGI) were used to assess function performance; the Berg Balance Scale (BBS) and the Biodex Fall Risk Index (FRI) were used to evaluate balance; and the 16-item Fall Efficacy Scale-International (FES-I) was used to evaluate fear of falling. At baseline and after the treatment, all measurements were obtained. Results Both groups (A and B) revealed a substantial increase in functional performance through a decrease in TUG scores and an increase in DGI. Additionally, there was a decrease in the risk of falling through an increase in the BBS scores and a decrease in the FRI. Furthermore, there was a decrease in the fear of falling, as measured using the FES-I, after treatment, with superior improvement in Group A with a p-value of <0.001. Conclusion Systematic desensitization combined with a goal-directed paradigm has a superior effect on improving functional performance and reducing the risk of falling and the fear of falling in patients with stroke compared to a goal-directed paradigm alone.